LANGUAGE PRODUCTION ABILITY OF CHILDREN AGED 6 IN INSTITUTE OF PLAY INTERNATIONAL SCHOOL MAKASSAR - Amal, Rizal Alamsa; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
The aims of this research is to investigate the contribution of language production ability of children aged 4 years. In Indonesia, there are not many studies on children’s language ability. There are not many studies based in Indonesia, where Indonesia is a country with the most cultures in the world which is one of the factors that influence the ability of children’s production. This study explanined about sentence production. Sentence production begins with captures message from which speech will be produced, and then uses the sentence processing mechanism in language production subsystem. This study is about Language Production Ability of Children Aged 6. There are two problems to be solved in this study: (1) How is the ability of language production for children aged 6 in Institute of Play International School Makassar? (2) What are the language disorders of children aged 6 in Institute of Play International School Makassar in producing language? The method used in this research is qualitative descriptive method and psycholinguistics approach. This research involved four children. Technique analysis used in this research is syntactical and phonological analysis. This technique is used to analyze the sentence utterance by children aged 6 in Institute of Play International School Makassar. Based on findings, The children aged 4 in Institute of Play International School Makassar are able to speak with good structure of sentence and able to pronounce the words correctly.